Aprovechamiento de la madera de encino en México - de la Paz Pérez Olvera, Carmen; Dávalos Sotelo, Raymundo; Guerrero Cuacuil, Estela (Instituto de Ecología, A.C., 2016)
A description is made of the situation of oak wood use in México. The most recent statistics of standing forest volume and wood production are included. Reference is made of the distribution of this resource in the country. The subjects treated in this work are: utilization of oak wood (including cellulose, sawn wood, fuel, crossties, poles, piles, round wood, veneer and plywood), and the influence of the technological characteristics on its use. The exploitation of oakwood is discussed in the context of the international market.It is concluded that the conservation of oak forests is an urgent task to preserve the ecological equilibrium of its growing areas.